Pengaruh Pengaruh Sudut Kemiringan Head Turbin Ulir Terhadap Daya Putar Turbin Ulir Dan Daya Output Pada Pembangkit Listrik Tenaga Mikro Hidro - Juliana, I Putu; Weking, Antonius Ibi; Jasa, Lie (Majalah Ilmiah Teknologi Elektro; Vol 17 No 3 (2018): (September - Desember) Majalah Ilmiah Teknologi Elektro, 2018)
The dependence of power plants on energy sources such as diesel, natural gas and coal is almost 75%, encouraging the development of renewable energy in an effort to meet the electricity supply. One of them is the micro hydro power plant by utilizing the potential of existing water. The working principle of PLTMH is to change the potential energy of water into electrical energy. In this final project has been designed modeling of micro hydro power plant by using screw turbine (Archimedes Screw). The turbine used resembles a drill bit, with a diameter of a turbine of 26 cm, a screw width of 10 cm, and an amount of 10 pieces of blade. Measurements made on the modeling of micro hydro power plants include: water discharge, turbine rotation, generator rotation, voltage, current, torque and generator output power and efficiency. The parameters are measured by changing the water fall on the turbine from the position of the turbine head angle 0 0 , 10 0 , 15 0 , 20 0 , 25 0 , 30 0 , 35 0 , 40 0 , 45 0 , 50 0 , 55 0 , 60 0 , 70 0 , 80 0  and 90 0 . The result of measurement that has been done on the parameters of micro hydro power plant modeling, obtained the highest measurement result at the corner of turbine head 40 0 . The output power generated is 10.92 watts, torque is 0.60 Nm and efficiency of 14%. The results obtained are still low because the turbine rotation is less able to rotate the generator, where the generator torque is greater than the torque in the turbine. This is influenced by the small water discharges in the modeling of this micro hydro power plant.